Influence of geometric patterns of microstructured superhydrophobic surfaces on water-harvesting performance via dewing - Seo, Donghyun (Langmuir : the ACS journal of surfaces and colloids, 2014)
On superhydrophobic (SHPo) surfaces, either of two wetting states-the Cassie state (i.e., nonwetted state) and the Wenzel state (i.e., wetted state)-can be observed depending on the thermodynamic energy of each state and external conditions. Each wetting state leads to quite a distinctive dynamic characteristic of the water drop on SHPo surfaces, and it has been of primary interest to understand or induce the desirable wetting state for relevant thermofluid engineering applications. In this study, we investigate how the wetting state of microstructured SHPo surfaces influences the water-harvesting performance via dewing by testing two different patterns, including posts and grates with varying structural parameters. On grates, the observed Cassie wetting state during condensation is well described by the thermodynamic energy criteria, and small condensates can be efficiently detached from the surfaces because of the small contact line pinning force of Cassie droplets. Meanwhile, on posts, the observed wetting state is dominantly the Wenzel state regardless of the thermodynamic energy of each state, and the condensates are shed only after they grow to a sufficiently large size to overcome the much larger pinning force of the Wenzel state. On the basis of the mechanical force balance model and energy barrier consideration, we attribute the difference in the droplet shedding characteristics to the different dynamic pathway from the Wenzel state to the Cassie state between posts and grates. Overall, the faster droplet shedding helps to enhance the water-harvesting performance of the SHPo surfaces by facilitating condensation on the droplet-free area, as evidenced by the best water-harvesting performance of grates on the Cassie state among the tested surfaces